Financial Knowledge Moderating The Effect Of Money Attitude On Personal Financial Management Behavior Of Students - Dwi Kumalasari; Muhadjir Anwar (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Attitude towards money or what is often called money attitude is an individual's perception of money based on his state of mind. This study aims to determine the level of personal financial management of students which influenced by attitudes with financial knowledge as a moderation medium. The research method used in this study was a quantitative method. Undergraduate students of Management Study Program in the UPN